Food, Tourism and Health: a Possible Sinergy? - Silvana Hrelia (Almatourism, 2015)
Food is a significant aspect of the tourist’s experience of a destination. While the term “wine and food tourism ” is too often addressed only to the taste of the product, the more aseptic definition of “food tourism” wants to focus the attention also on the health properties of local products. Healthy eating is not about strict nutrition philosophies, staying unrealistically thin, or depriving ourselves of the foods we love. Rather, it is about feeling great, having more energy, stabilizing our mood, and keeping ourselves as healthy as possible, all of which can be achieved by learning some nutrition basics and using them in a way that works for us. We can expand our range of healthy food choices and learn how to plan ahead to create and maintain a tasty, healthy diet. Not only the psychological, but also the physical benefits of tourism appear to have gained increasing importance and healthy nutrition represents one of the most important determinants. Food tourism can be considered a potential benefit for human health.Understanding tourists’ needs and wants in terms of healthy food consumption is of paramount importance to hospitality businesses. Food, tourism and health could really be a possible synergy.